2020
DOI: 10.3389/feart.2020.00347
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Catchment-Scale Nitrogen Losses Across a Land-Use Gradient in the Subtropics

Abstract: Changing land use in subtropical and tropical catchments to farmland can result in higher nitrogen (N) loss to aquatic ecosystems. Here, we developed a lumped water and N balance model to estimate regional N losses to creeks at catchment scale within understudied subtropical catchments in Australia. The conceptual water balance model CoCa-RFSGD was extended by the nitrogen mass balance in top and subsoil by adding nitrogen cycle transformation estimates depending on meteorological, soil, and land-use propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Moreover, the selected period for calibration and validation process was due to lack of in-situ data spanning the model duration. During calibration (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003), four iterations each with no less than 500 simulations were executed to refine the model parameters (Abbaspour, 2015;Hajati et al, 2020). With each iteration performed, values of each parameter range become smaller approaching the best solution and achieving better models than previous iterations.…”
Section: Calibration Validation and Uncertainty Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the selected period for calibration and validation process was due to lack of in-situ data spanning the model duration. During calibration (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003), four iterations each with no less than 500 simulations were executed to refine the model parameters (Abbaspour, 2015;Hajati et al, 2020). With each iteration performed, values of each parameter range become smaller approaching the best solution and achieving better models than previous iterations.…”
Section: Calibration Validation and Uncertainty Analysismentioning
confidence: 99%
“…Where Q is the variable under observation or simulation, that is discharge, and are discharge data, which have been measured and simulated respectively, while n refers to the number of total records and ̅ denotes the average measured data while i is the ith measured or simulated data. Similar to the P-factor and R-factor, there are no specific numbers to achieve, however, the recommended values for watershed scale (Gupta et al, 2009;Hajati et al, 2020;Moriasi et al, 2007Moriasi et al, , 2015 are as follows;…”
Section: ∑ (mentioning
confidence: 99%
“…Agricultural fertilization and urban wastewater discharge directly expose Nr to the environment 26 ; climate and topography contribute to Nr loss by driving Nr transport 11 ; changes in land use composition and structure can also affect Nr loss by altering surface nutrient content and nutrient transport 27 . Research has shown that the Nr loss has increased 3.5-fold due to agricultural intensification 28 , and increased impervious surfaces have also exacerbated Nr losses 29 . Moreover, the shift from forest to cleared land increases the denitrification capacity 28 ; and increasing the patch edges of grassland can reduce Nr pollution 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the Nr loss has increased 3.5-fold due to agricultural intensification 28 , and increased impervious surfaces have also exacerbated Nr losses 29 . Moreover, the shift from forest to cleared land increases the denitrification capacity 28 ; and increasing the patch edges of grassland can reduce Nr pollution 30 . However, traditional research tools and methods such as multiple linear regression, correlation analysis, ordinary least squares models, spatial lag models, and spatial error models are challenging to deal with drivers' spatial variability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its performance and functionality described in the preceding paragraphs, the SWAT model was used mainly because it has a multidimensional methodology to assess the catchment water yield, baseflow, and surface runoff [40]. To evaluate the LULC effect on hydrological flow, the SWAT model has better performance during a simple water balance approach [41,42]. In semi-arid climate areas, the curve number (CN) simulating method of the SWAT model performed well in estimating surface runoff at high precipitation intensity, although the model underestimated surface runoff [43].…”
Section: Introductionmentioning
confidence: 99%